Creative metaphors in video lessons: the relationship between the novel and the conventional / Metáforas criativas em videoaulas: a relação entre o novo e o convencional (Revista de Estudos da Linguagem, 2020)
Abstract: The metaphors used in non-poetic contexts are mostly conventional. This study, which is part of a broader research, analyzes the emergence of – and the relationship between – conventional and novel/creative metaphors in Biology video lessons. The theoretical basis is composed of the Theory of Conceptual Metaphor (LAKOFF; JOHNSON, 2002; LAKOFF; TURNER, 1989) and the Perspective of Metaphor in Discourse (SEMINO, 2008). Thus, the general objective of this paper is to verify the emergence of conceptual and linguistic metaphors produced by teachers in Biology video lessons, as well as to analyze their degree of novelty and/or conventionality. The data analyzed came from YouTube video subtitles, and the methodology used to identify metaphors in speech was the MIP (PRAGGLEJAZ GROUP, 2007). The results indicate that creative metaphors are present in the discourse of these teachers and play a relevant role in the presentation of scientific content.Keywords: metaphor; creativity; conventionality; video lessons; textual patterns.Resumo: As metáforas empregadas em contextos não poéticos apresentam-se majoritariamente de forma convencional. O presente estudo, que faz parte de uma pesquisa mais abrangente, trata da análise da emergência de – e da relação entre – metáforas convencionais e novas/criativas em videoaulas de Biologia. O aporte teórico é composto pela Teoria da Metáfora Conceptual (LAKOFF; JOHNSON, 2002; LAKOFF; TURNER, 1989) e pela Perspectiva da Metáfora no Discurso (SEMINO, 2008). Desse modo, o objetivo geral deste artigo é verificar a emergência de metáforas conceptuais e linguísticas produzidas por professores em videoaulas de Biologia, assim como analisar seu grau de novidade e/ou convencionalidade. Os dados analisados são provenientes de legendas de videoaulas do YouTube, e a metodologia empregada na identificação de metáforas no discurso foi o MIP (PRAGGLEJAZ GROUP, 2007). Os resultados indicam que metáforas criativas estão presentes no discurso desses professores e desempenham um papel relevante na apresentação de conteúdos científicos.Palavras-chave: metáfora; criatividade; convencionalidade; videoaulas; padrões textuais.